2011
DOI: 10.1080/02626667.2011.629783
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands

Abstract: It is widely recognized that healthy ecosystems can provide considerable benefits to people, including food, timber, freshwater, protection from floods and much of what we call quality of life. A global review of these ecosystem services carried out as part of the Millennium Ecosystem Assessment (MEA) provided a framework for national and local studies. Using the MEA approach, this paper reviews the ecosystem services provided by the Somerset Levels and Moors wetland system in southwest England. This wetland p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…As this work has shown, the precision of individual sensors must be considered when dealing with such small differences. Wicken Fen may also be said to be providing a climate regulation ecosystem service, as identified by Acreman et al (2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this work has shown, the precision of individual sensors must be considered when dealing with such small differences. Wicken Fen may also be said to be providing a climate regulation ecosystem service, as identified by Acreman et al (2011). …”
Section: Discussionmentioning
confidence: 99%
“…Huryna et al (2014) measured 30% more evaporation from a wet meadow than from pasture and arable fields, suggesting this contributes significantly to the cooling of agricultural landscapes. Acreman et al (2011) identified a lower temperature within the Somerset Levels and Moors, UK, compared to outside the wetland as a result of higher evapotranspiration and Raney et al (2014) identified significantly different soil temperatures within temperate fens relative to surrounding uplands.…”
Section: Microclimate Effectsmentioning
confidence: 99%
“…The SLMs cover an area of 650 km 2 and consist of low-lying organic peat soils underlain by marine silts and clays, which form an impermeable sub-layer. They are the largest remaining area of lowland wet grassland in England (more than 20% of the resource) and include 18 Sites of Special Scientific Interest (SSSIs) covering 7200 ha, 12 of which (6300 ha) are Special Protection Areas under the European Habitats Directive, with most of the area designated as a Ramsar site under the International Convention on Wetlands (Acreman et al, 2011).…”
Section: The Study Sitementioning
confidence: 99%
“…Whilst raising water levels may support delivery of some ecosystem services, others may be lost or reduced. Acreman et al, (2011) looked at the effect of various management practices on the extensively drained Somerset Levels and Moors and found that raised water levels increased delivery of services, such as carbon sequestration, climatic regulation, biodiversity (in the long term) and recreation and education. They also found that food production, freshwater availability, biodiversity (in the short term) and flood storage were reduced.…”
mentioning
confidence: 99%
“…Phosphorus removal has been shown to correlate positively with an increase in wetland area, and a minimum wetland to farmyard area ratio of 1.3 has been proposed for effective removal of molybdate reactive phosphorus (MRP) [11]. When deciding on wetland size, other factors such as ecosystem services [12,13] should also be considered as discussed below.…”
Section: Introductionmentioning
confidence: 99%